2017
DOI: 10.3390/molecules22101728
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Treatment Reduces Oxidative Damage and Normalizes Plasma Pro-Inflammatory Cytokines in Patients Suffering from Charcot-Marie-Tooth Neuropathy: A Pilot Study in Three Children

Abstract: Charcot-Marie-Tooth neuropathy (CMT) is a motor and sensory neuropathy comprising a heterogeneous group of inherited diseases. The CMT1A phenotype is predominant in the 70% of CMT patients, with nerve conduction velocity reduction and hypertrophic demyelination. These patients have elevated oxidative stress and chronic inflammation. Currently, there is no effective cure for CMT; herein, we investigated whether melatonin treatment may reduce the inflammatory and oxidative damage in CMT1A patients. Three patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…These studies suggest that GDAP1 acts as a sensor of the reduced to oxidized glutathione ratio (GSH/GSSG) participating in the release of an antioxidative response causing the recovery of GSH/GSSG. These results suggest a possible role of oxidative stress and chronic inflammation in the pathogenesis of GDAP1-related CMT, as shown to occur in other forms of CMT such as CMT1A [30] or CMT1C [31].…”
Section: Proposed Roles Of Ganglioside-induced Differentiation-assmentioning
confidence: 65%
“…These studies suggest that GDAP1 acts as a sensor of the reduced to oxidized glutathione ratio (GSH/GSSG) participating in the release of an antioxidative response causing the recovery of GSH/GSSG. These results suggest a possible role of oxidative stress and chronic inflammation in the pathogenesis of GDAP1-related CMT, as shown to occur in other forms of CMT such as CMT1A [30] or CMT1C [31].…”
Section: Proposed Roles Of Ganglioside-induced Differentiation-assmentioning
confidence: 65%
“…Moreover, said results would be in line with improvements obtained in CMT1A after administering another antioxidant and anti-inflammatory with mitochondrial benefits, such as melatonin. Particularly in this last study, improvements in oxidation state and inflammation levels [ 27 ] were observed after 3 months of treatment. IL-6 levels were also established within normal values, coinciding with our results after administering EGCG.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, these patients also suffer from acute, subacute or chronic inflammation along with oxidative stress (i.e., ROS) that is involved with progression of the disease [ 217 , 218 , 219 , 220 , 221 ]. Interestingly, melatonin treatment in CMT neuropathy patients reduces oxidative damage and normalizes plasma proinflammatory cytokines such as IL-1β [ 217 ]. This reduction in inflammasome activation may correlate with reduction of the degenerative process.…”
Section: Other Rare Neuromuscular Diseasesmentioning
confidence: 99%